An IoT based system for vehicle allocation and unlocking using android application with RTDM for smart transportation - A.R, Aswathi; R.Umamageswari, S.; Sambath, K. (International Journal of Engineering and Technology, 2019)
An Internet of Things (IoT) technology based smart vehicle management system using android application is used for allocating, unlocking and real time data monitoring (RTDM) mode. This system delivers the information about availability, allocation, and unlocking of vehicles. IoT technology provides a path between user and server for selecting vehicle through mobile app and to unlock the vehicle. Also, between admin and front-end module to monitor the vehicles through website. Special Android app (Trackit) is designed for an easy access of user in their smart phone. Company App have facility to list out the availability of vehicles and can allocate vehicle as per the request from driver. Unlocking of vehicle from parking slot is from Android app according to the command from server after authentication of the driver is another highlight of the system. Administrator can track the details of on-running vehicles from company website with the help of front-end controller affixed in vehicle. The status of company vehicles is stored in database and it can be retrieved by administrator as per the requirement. In future, this system is a best solution for commercial transportation which directly benefits transportation arms of logistics, fleet management and supply chain system.Â Â Â